Challenges of Male Students of Home Economics in Tertiary Institution in Anambra State - Eugenia N., Emeka Okafor (Journal of Home Economics Research, 2024)
This study investigated the challenges faced by male students of Home Economics in tertiary institutions in Anambra state. Five research questions were answered. It adopted a survey research. The population for the study was 260 students offering Home Economics as a course of study. 155 students was selected through random sampling. Questionnaire was used for data collection. Data were analysed using mean. Findings include among others, family related challenges, society related challenges, self and peers related challenges. It was recommended that adequate enlightenment programmes should be given to the public on prospects and career opportunities in Home Economics, parents should not discriminate among their children on choice of courses and government should pay adequate attention to Home Economics education by providing funds, equipment and training of the teachers.